ANALYSIS OF TEACHER PROFESSIONAL COMPETENCE IN UTILIZING INFORMATION AND COMMUNICATION TECHNOLOGY - Yoan Tamara; Hermansyah Hermansyah; Marleni Marleni (Universitas PGRI Palembang, 2024)
In the industrial era 4.0, information and communication technology can be used optimally to achieve good efficiency, almost all industries and agencies have used digital media. In the world of education, technology is developing rapidly after the Covid-19 pandemic, because the pandemic has forced digital changes in the world of education and we need a good understanding and knowledge about the types of students who use digital technology in the learning process. Information and communication technology is a multimedia-based learning medium technology involving text, images, sound, video and the internet. From this background, there are 2 formulations of the problem How do teachers use information and communication technology in the learning process and what are the factors that become obstacles when using ICT. This research is qualitative research and data collection is done using observation, interview tests, student assessment questionnaires against teachers and documentation. This research was conducted to analyze professional teachers who are competent in using information and communication technology in the learning process. The subjects and informants of this study were English teachers and students of class X Mia 1 and Mipa 2. The conclusion obtained after conducting interviews with English teachers and students is that in almost every meeting they use information and communication technology as a learning medium to assist teachers in explaining or describing the material to be taught so that students can easily understand the material presented and motivate students to be more creative and active in the process of learning and learning by =using information and communication technology to, help students find broader information and make it easier for them to communicate during the learning process. English teachers are sufficiently proficient in ICT-based learning media when the learning takes and use media according to the teaching material.